DO MARKETS HEAR THE SIGNAL? EXCHANGE RATE REACTIONS TO ECB QUANTITATIVE EASING ANNOUNCEMENTS - Šafár, Leoš; Sopko, Jakub (Veredas do Direito, 2025)
This paper examines the short-term effects of quantitative easing (QE)–related announcements by the European Central Bank (ECB) on the euro’s exchange rate against major currencies. Employing a standard event-study methodology based on daily data from 2015 to 2018, the analysis measures abnormal changes in 14 euro exchange rate pairs following ECB press releases and press conferences explicitly addressing QE. Results indicate that announcements concerning the continuation or expansion of QE programmes typically led to a depreciation of the euro, while statements signalling tapering or normalization triggered short-term appreciations. These asymmetric reactions confirm that the signalling and portfolio rebalancing channels dominate the FX transmission of QE. Moreover, the volatility of responses declined over time, suggesting that markets progressively internalized QE as a structural element of the monetary policy framework. The findings contribute to the literature by extending event-study evidence to the euro’s foreign exchange dynamics and offer insights for policymakers seeking to manage expectations and communication during unconventional monetary interventions. The results also provide a forward-looking benchmark for anticipating currency market behavior should balance-sheet policies be reintroduced in future periods of macroeconomic stress.